The ballad of Ed and Lewis: conflictual mimesis and the revocation of the social contract in James Dickey's Deliverance. Issue 1 (2nd January 2016) - Wilson, Eric
Abstract : This paper provides a close critical reading of the novel Deliverance (1970) by James Dickey from the perspective of law and literature. It employs the critical literary theory of René Girard in suggesting that Deliverance may be usefully understood as an interrogation, or even a satire, of the Hobbesian doctrine of the social contract. Whereas Hobbes raises the possibility, but then conspicuously fails to adequately theorize, the concept of the 'little monarchy' or the private sovereignty of one man in the wilderness, Deliverance is wholly premised upon both the feasibility and the desirability of man-the-hunter-as-sovereign. A close reading of the novel detects the employment of a number of critical notions of Girard – the crisis of undifferentiation, conflictual mimesis, the monstrous doubles – that collectively serve to undermine the facile assumption of the universality of the social contract as well as any clear demarcation between the realms of sovereignty and crime.